2011
DOI: 10.1002/ijc.25460
|View full text |Cite
|
Sign up to set email alerts
|

HYAL1 overexpression is correlated with the malignant behavior of human breast cancer

Abstract: Extracellular matrix (ECM) is closely correlated with tumor cell growth, proliferation, metastasis and angiogenesis, etc. Hyaluronic acid (HA) is a component of the ECM, and hyaluronidase (HAase) is a HA-degrading endoglycosidase. Levels of HAase are elevated in many cancers. Hyaluronidase-1 (HYAL1) is the major tumor-derived HAase. In this study, we detected HYAL1 expression levels in breast cancer cells and tissues, and measured the amount HAase activity in breast cancer cells. Compared with nonmalignant bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 50 publications
5
99
0
1
Order By: Relevance
“…HAase levels were demonstrated to be elevated in breast tumors, and RT-PCR analysis has detected the expression of HYAL2 and HYAL3 in breast cancer tissues, 34 suggesting an association between HAase and the tumor invasive/metastatic phenotype. 35,36 In accordance with the data from the present study demonstrating higher levels of HYAL2 in breast cancer cell lines compared with nontumorigenic cell line 184A1, previous reports have shown that, whereas less invasive breast cancer cells expressed HYAL3, highly invasive cells expressed HYAL2. 34 Although the promoter region of these genes is characterized by a CpG island, their expression levels were not significantly increased after the treatments with the demethylating agents in our study.…”
Section: Discussionsupporting
confidence: 92%
“…HAase levels were demonstrated to be elevated in breast tumors, and RT-PCR analysis has detected the expression of HYAL2 and HYAL3 in breast cancer tissues, 34 suggesting an association between HAase and the tumor invasive/metastatic phenotype. 35,36 In accordance with the data from the present study demonstrating higher levels of HYAL2 in breast cancer cell lines compared with nontumorigenic cell line 184A1, previous reports have shown that, whereas less invasive breast cancer cells expressed HYAL3, highly invasive cells expressed HYAL2. 34 Although the promoter region of these genes is characterized by a CpG island, their expression levels were not significantly increased after the treatments with the demethylating agents in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In BCA, HYAL-1 and HYAL-2 are often coordinately overexpressed compared to non-malignant breast tissue. Knockdown of HYAL-1, which is overexpressed in MDA-MB-231 and MCF-7 BCA lines, reduces tumour xenograft size (Tan et al, 2010). 3. HA receptors detect oligosaccharides and fragments: Control of key signalling pathways by HA fragments 3.1 CD44 CD44 is a class I transmembrane receptor, which binds to HA via a link domain and is expressed by a variety of cells, including fibroblasts, endothelial and epithelial cells, smooth muscle, and haematopoietic cells.…”
Section: Ha Fragmentation and Its Role In Tumourigenesismentioning
confidence: 99%
“…In general, high MW HA inhibits angiogenesis while fragments promote angiogenesis. Overexpression of HA and HYALs has been linked to an increase in angiogenesis in several types of cancers including breast (Tan et al, 2010), bladder (Lokeshwar et al, 2000, Golshani et al, 2008, prostate (Ekici et al, 2004, Bharadwaj et al, 2007, and endometrial (Paiva et al, 2005). Koyama et al (2007) demonstrated that an increase in HAS2 expression by genetic modifications in a mouse model of BCA causes a higher incidence of adenocarcinoma accompanied by an increase in angiogenesis (Koyama et al, 2007).…”
Section: Angiogenesismentioning
confidence: 99%
“…There is a complex interrelationship among angiogenesis, hyaluronic acid, and certain enzymes, 3 Presence of higher-than normal amounts of hyaluronic acid facilitates the growth and spread of the tumor in several ways. It is extremely hydrated, facilitating the passage of nutrients into and wastes from tumor cells until the tumor reaches the critical size at which passive diffusion is no longer enough.…”
Section: Introductionmentioning
confidence: 99%